Hierarchical coordinated energy management strategy for electricity-hydrogen integrated charging stations based on IGDT and hybrid game - Cai, Pengcheng (2023)
The popularity of environment-friendly vehicles promotes the rapid development of electric and hydrogen integrated charging stations (EHI-CSs), which makes the power system face unprecedented challenges. Optimized and effective management strategies are needed to coordinate the operation among EHI-CSs and the distribution system operator (DSO). To this end, a bi-level energy management framework is proposed for DSO and EHI-CSs. The framework takes DSO as the leader of the upper game and provides dynamic differential pricing for EHI-CSs, while EHI-CSs work as the followers, react to the leader's decision in the manner of Nash-Harsanyi bargaining game. Moreover, aiming at the uncertainty of photovoltaic, a risk aversion robustness model for EHI-CSs is designed with information gap decision theory. A two-stage solution is proposed to solve the nonlinear bi-level programming problem with hierarchical energy interaction. Firstly, the lower-level energy cooperation is equivalent to two sub-problems of coalition's profit maximization and payment bargaining, the bisection approach is employed to distributed solve the energy pricing problem in the first stage with tie-line power and prices being the only exchange information. Then the second stage determines the payment according to the scheduling results. Numerical simulations verify the effectiveness of the proposed model and algorithm.